Freight Transport and Distribution Concepts and Optimisation Models - Bektas, Tolga (CRC Press, Taylor & Francis Group, 2017)
This book serves as a primer on freight transportation and logistics, providing a general and broad coverage of concepts, mathematical models and methodologies available for freight transportation planning at strategic, tactical and operational levels. It is aimed at graduate students, and is also a reference book for practitioners in the field. The book includes preliminaries, such as mathematical modeling and optimisation algorithms. The book also features case studies and practical real-life examples to illustrate applications of the concepts and models covered, and to encourage a hands-on and a practical approach. The author has taught and published extensively in the field and draw on state-of-the-art scientific research. He has also been part of a number of practical research projects, which underpin the real life examples in the boo